Hand, foot, and mouth disease: could EPs® 7630 be a treatment option? A prospective randomized open-label multicenter clinical study - Sütçü, Murat; Kara, Manolya; Yıldız, Funda; Kılıç, Ömer; Tural Kara, Tugce; Akkoc, Gulsen; Büyükçam, Ayşe; Elmas Bozdemir, Şefika; Özgür Gündeşlioğlu, Özlem; Gül, Doruk; İseri Nepesov, Merve; Kara, Ateş (Frontiers in Pediatrics, 2024)
Purpose: Hand, foot and mouth disease (HFMD) is a viral contagious disease of children caused by human enteroviruses (EVs) and coxsackieviruses (CVs). There is no specific treatment option for HFMD. EPs®7630's anti-infective and immunomodulatory properties have previously been demonstrated in several in vitro and in vivo studies; however, the use of this herbal medicine in children with HFMD has not previously been investigated.Methods: This prospective randomized multicenter clinical study included 208 children with HFMD.The diagnosis was made by pediatricians. The patients who were within the first 48 hours of symptom onset (according to the first onset of fever and skin findings) were enrolled. The study participants were assigned into 2 groups as EPs®7630 and control groups. All patients were followed up twice more, 48 hours after the first admission and on the 5th-7th day. Another phone evaluation was conducted for those with continued complaints from the previous visit.The median age was 27 (12-112) months. The male-female ratio was 0.98. One hundred thirty one (63%) of 190 patients had no history of household contact. EPs®7630 group included 94 and control group included 96 patients. A significant difference was found between the groups in terms of complaint scores at the visits made at the 48th hour of the treatment and on days 5-7 (p<0.001). The mean±SD disease duration of EPs®7630 users was significantly shorter 6.07±0,70 days (95 Cl%: 5.92-6.21)] than the control group [8.58±0,94 days (95 Cl%: 8.39-8.77)] (p<0.001). Besides, the hospitalization rate among the EPs® 7630 users were significantly lower (p=0.019). No side effects were observed, except for unpleasant taste, which was reported in 5 patients [EPs® 7630 group] Conclusion: Considering its efficacy and safety profile EPs® 7630 may represent a feasible herbalbased treatment option for children with HFMD.